The contribution of Lana de Souza Cavalcanti to the teaching of Geography (PerCursos, 2025)
In this article, we examine aspects of Lana de Souza Cavalcanti’s perspective on geography education, with an emphasis on the teaching and learning of geographic concepts, including the concept of territory. Through documentary and bibliographic research, we aim to identify the contributions of Lana de Souza Cavalcanti, who has stood out in the field since the 1990s for her pioneering work and representativeness in the development of a Didactics of Geography in Brazil. We highlight her proposal for conceptual instrumentalization grounded in Vygotsky’s theoretical framework, as well as her indication that the city and citizenship education can serve as central themes for organizing the teaching of territory. The renowned professor from Goiás emphasizes the need to move beyond the ideological construction of territory as merely synonymous with "national territory." In doing so, she aligns with the ideas of Claude Raffestin, asserting that students who have internalized the concept of territory, equipped with theoretical tools, will be able to relate them to their everyday experiences. This enables each individual to recognize their capacity to intervene in the territory at various scales.
Keywords: geography teaching; geography didactics; Lana de Souza Cavalcanti